CONTRIBUTION AND POTENTIAL OF CROWDFUNDING "KITABISA.COM" AS AN ALTERNATIVE HEALTH FINANCING IN INDONESIA - Persada, Bintang; Marini; Fedryansyah, Muhammad; Hairunisyah; Finanda, Ressha; Putri, Rufina Eka (Progress In Social Development, 2025)
Health services are one type of service available in Indonesia. The Social Security Organising Agency (BPJS) is an institution established by the Indonesian government to help the community in the health sector, but BPJS is currently unable to fully finance the needs of the community in health services or facilities. Therefore, other alternative financing is needed, one of which is Crowdfunding Kitabisa.com, which has helped the Indonesian people in financing health services. The purpose of this study is to describe the contribution of Crowdfunding Kitabisa.com in health financing and to describe the potential development of crowdfunding. The research method used is descriptive qualitative with data collection using literature review techniques. The results showed that Crowdfunding Kitabisa.com has contributed as a fundraising platform, and this shows its role as an alternative in financing in the health sector. This crowdfunding has the potential to be developed due to limited access to modern health services, high health costs, the growth of technology and internet access, as well as social awareness and community solidarity. The implications of this research for social welfare include crowdfunding as a means of increasing health accessibility, community empowerment, innovation in health financing, and increasing awareness of social solidarity.